2017
DOI: 10.1021/acs.organomet.7b00668
|View full text |Cite
|
Sign up to set email alerts
|

Role of σ,π-Digold(I) Alkyne Complexes in Reactions of Enynes

Abstract: Gold(I) acetylide and σ,π-digold(I) alkyne complexes derived from one prototypical 1,6-enyne and from 7-ethynyl-1,3,5-cycloheptatriene have been prepared and structurally characterized. Their possible role in gold(I)-catalyzed cycloisomerizations has been studied by experiment and by DFT calculations. Gold(I) acetylides are totally unproductive complexes in the absence of Brønsted acids. Similarly, no cyclizations were observed by heating σ,π-digold(I) alkyne digold(I) at least up to 130 °C. Theoretical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 78 publications
(93 reference statements)
3
24
0
Order By: Relevance
“…The use of tetraarylborate (BAr F ) as the anion was also found to be important to obtain consistently good yields . Kinetic experiments suggested that the deprotonation of terminal alkynes 132 is slower with this bulky anion, which minimizes the formation of undesired σ,π‐digold(I) alkyne complexes ,…”
Section: Development Of An Enantioselective Intermolecular [2+2] Cyclmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of tetraarylborate (BAr F ) as the anion was also found to be important to obtain consistently good yields . Kinetic experiments suggested that the deprotonation of terminal alkynes 132 is slower with this bulky anion, which minimizes the formation of undesired σ,π‐digold(I) alkyne complexes ,…”
Section: Development Of An Enantioselective Intermolecular [2+2] Cyclmentioning
confidence: 99%
“…[48b] Kinetic experiments suggested that the deprotonation of terminal alkynes 132 is slower with this bulky anion, which minimizes the formation of undesired s,p-digold(I) alkyne complexes. [50,51] The same gold(I) complex was used for the first intramolecular reaction of large enynes that leads to macrocycles by a [2 + 2] cycloaddition. [141] Thus, for example, 1,12-enyne 135 gave 11-membered ring macrocycle 136 a (Scheme 31).…”
Section: Development Of An Enantioselectivementioning
confidence: 99%
See 1 more Smart Citation
“…One year later, the Gasgosz's group studied a similar reactivity for the phosphinegold(I) catalyst highlighting its unusual dual character as nucleophile (C–H activation) and electrophile (alkyne activation) . These pioneering discoveries in cyclisation reactions with allenyne and dyines, which contain a C–C triple bond, enabled gold to form the so‐called σ,π‐digold‐acetylide complex , . This latter complex represented a landmark together with the introduction of N‐heterocyclic carbene (NHC) ligands by means of the stable gem‐diaurated [{Au(NHC)} 2 (µ‐OH)] species discovered by Nolan and co‐workers in 2013 .…”
Section: Introductionmentioning
confidence: 99%
“…Among others, silver salts are the most used agents for this purpose (Ranieri et al, 2015). Furthermore, both the electronic nature of ligands (Wang et al, 2012; Ebule et al, 2016; Gung et al, 2016; Ferrer and Echavarren, 2018a) and of the counterion (Homs et al, 2014; Ciancaleoni et al, 2015; Jia and Bandini, 2015; Rocchigiani et al, 2015; Gatto et al, 2016; Yuan et al, 2018; Schießl et al, 2018a,b) have a significant influence on the reactivity of the gold-catalyzed processes.…”
Section: Introductionmentioning
confidence: 99%